Study on Bus Robbery Occurrences in Belém do Pará, Brazil: an analysis from the victims' profile, characteristics and probabilities (Research, Society and Development, 2020)
News about bus robbery has become frequent in several Brazilian municipalities. The intensification in this type of crime is causing fear and a feeling of insecurity for the population, especially when the victims are the drivers and collectors, as they are exposed daily to public precariousness and its effects. In this context, the present study aimed to feature the profile of bus drivers and collectors, victims of robbery in their work, in five municipalities in the Metropolitan Region of Belém, state of Pará, Brazil, in the years 2017 and 2018 and to verify possible associations between the municipality of occurrence, shift and day of the week with the environment employed to commit the crime. There fore, we used the statistical techniques exploratory data analysis and correspondence analysis, where it was found that the main results are that most of the victims are male, have completed high school, the most common means used to commit the crime it is the firearm and the shift with the highest rate of assault is the night shift. However, it was concluded that public policies on public security that aim to face and curb the crime of bus robbery in the Metropolitan Region of Belém are extremely important.